In-vitro evaluation of probiotic potential of gut microbes isolated from retail chicken - Sangram Biswas; Lutfor Rahman; Md. Taofiqur Rahman; Susmita Chowdhury; Fahmida Khatun; Azimun Nahar; Sabina Yasmin (PLoS ONE, 2026)
Probiotics are live, non-pathogenic microorganisms that help to improve the host’s gut health when administrated in sufficient proportions and are now serving as effective alternatives to antibiotics for managing animal infections and enhancing production. The objective of this study was to isolate, identify and characterize lactic acid bacteria (LAB) strains with excellent probiotic properties from the gastrointestinal tract (GIT) of retail broiler chickens. Samples were enriched in MRS broth at 37°C and plated on MRS agar to isolate distinct colonies of potential probiotic candidates. The isolates underwent a series of standard morphological and biochemical analysis to fulfill the criteria for presumptive identification of LAB and probiotic characteristics. These analyses included Gram staining, catalase testing, hemolytic activity assays, tolerance assays to NaCl, simulated gastric juice and bile salts, antagonistic activity assays, antibiotic susceptibility testing, cell adhesion assay and genotypic identification through 16S rRNA gene sequencing. A total of 40 microbial strains were isolated from the GIT of 20 retail broiler chickens. Among these, 4 LAB strains showed the best probiotic results and were genotypically identified as Enterococcus faecium MCI7, Pedicoccus pentosaceus MCI10, Pediococcus pentosaceus MCC6 and Pediococcus pentosaceus MCC12. The selected strains exhibited non-hemolytic activity and were able to survive in simulated gastric juice at pH 3. Furthermore, the strains displayed bile salt tolerance in the presence of 0.3% bile salt for 4 hours, ranging from 21.91 to 32.77% and a wide range of antimicrobial activities against various pathogenic bacterial strains with inhibition zones ranging from 10 to 16.5 mm. Moreover, three P. pentosaceus strains (MCI10, MCC6, MCC12) were sensitive to most of the tested antibiotics and demonstrated good adherence abilities. Our study identified four LAB strains as promising probiotic candidates for poultry feed additives to effectively establish intestinal microflora, enhance meat quality and growth, and control pathogens.